Journey to the literary work of Júlio Dinis: visit to the Júlio Dinis Museum – An Ovar House - Silva, Ana (2017)
This article aims to highlight the relationship between tourism and literature, namely, the contribution of visits to the author’s houses. The choice fell on the Júlio Dinis Museum – An Ovar House, which, in addition to honoring the writer Júlio Dinis, valuing his passage through Ovar, where he was inspired to write part of his work, preserves the structure of the nineteen century’s architecture. Thus, starting from the literary presupposition – knowing the writer and his work –, it is possible to discover a new tourist attraction, being a space which combines several aspects: scientific, aesthetic, cultural and economic.